Diagnosing Peripartum Cardiomyopathy in a Resource-Limited Setting, a Clinical Perspective: Case Report - Rahman, Tyfur; Tahia, Kazi Nazratun Nomany (Journal of Cardiology and Cardiovascular Medicine, 2024)
Peripartum cardiomyopathy is a rare case of heart failure with reduced ejection fraction and is considered a diagnosis of exclusion. The symptoms of heart failure in patients with peripartum cardiomyopathy can mimic the physiologic conditions of normal pregnancy. In an acute decompensated state, PPCM can present with acute severe upper abdominal or epigastric pain. We are presenting a 24-year-old female with no personal or family history of heart disease and no identifiable risk factor for PPCM. Based on her initial presentation in the emergency department, a diagnosis of acute severe pancreatitis was sought, and she was referred to the Intensive Care Unit. After further evaluation of the serological tests and imaging, she was eventually diagnosed as a case of PPCM. We emphasize the rare nature of the disease with a diverse presentation which poses a diagnostic challenge, especially in a resource-limited setting where advanced diagnostic tools may be restricted and socioeconomic condition poses a barrier to further patient evaluation. This case exemplifies the infrequent occurrence and atypical manifestation, presenting a learning opportunity for future clinicians.